Physician behavior under prospective payment schemes: Evidence from artefactual field and lab experiments - Hafner, Lucas; Reif, Simon; Seebauer, Michael (2017)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party representing the health insurance which finances medical service provision. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical services. We conduct a laboratory experiment in neutral as well as medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.<br
Keywords: health economic experiment; framing; physician behavior; prospective payment schemes